2022
DOI: 10.1101/2022.04.22.488943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineered extracellular matrices reveal stiffness-mediated chemoresistance in patient-derived pancreatic cancer organoids

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by its fibrotic and stiff extracellular matrix (ECM); however, the role that altered cell-ECM signaling may play in driving PDAC phenotype has historically been difficult to dissect. Here, we design an engineered matrix that recapitulates key hallmarks of the tumor ECM and show that patient-derived PDAC organoids develop gemcitabine chemoresistance when cultured within high stiffness matrices mechanically matched to in vivo tumors. Using genetic barcodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…This technology allows us to stiffen and soften a matrix and observe its effects on the same cell population longitudinally without the need for gel digestion and cell dissociation. 88 Here, using our platform technology, we found that, as expected, magneto-stiffening of the matrix promoted EMT and the hypoxic environment in tumor spheroids while it reduced drug sensitivity and tumor-killing effects. 12,89 However, during matrix softening on the same spheroid population, EMT was halted, and we observed a switch to MET based on the expression levels of E-/N-cadherin.…”
Section: Discussionsupporting
confidence: 72%
“…This technology allows us to stiffen and soften a matrix and observe its effects on the same cell population longitudinally without the need for gel digestion and cell dissociation. 88 Here, using our platform technology, we found that, as expected, magneto-stiffening of the matrix promoted EMT and the hypoxic environment in tumor spheroids while it reduced drug sensitivity and tumor-killing effects. 12,89 However, during matrix softening on the same spheroid population, EMT was halted, and we observed a switch to MET based on the expression levels of E-/N-cadherin.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, we also exploited the native biocompatibility of the NorHA hydrogel and the susceptibility of EAC PDOs to anti-cancer drugs to establish a novel in vivo model for targeted therapy studies. Whilst recent work has focused on understanding the role of engineered-ECM properties in tumor PDO (not EAC) resistance to therapy 23,[27][28][29] , we showed that our novel in vivo xenograft model allows for identification of matrix stiffness-dependent expression of transcription factors that can be exploited for targeted therapy in EAC. Therefore, this novel engineered organoid culture platform lays the foundation for application of therapeutics to disrupt contribution of ECM stiffness in EAC, and potentially, other cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, HA-based hydrogels have been used by other groups to study tumor progression and resistance to therapy of other cancer types (e.g. colorectal and pancreatic adenocarcinomas) 28,29,37 .…”
Section: Engineered Hydrogel Supports Eac Pdo Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this workflow did not involve 3D biomatrix, which could limit the use of this technique for application, such as tumour organoids, where a bio-matrix is critical to maintain cell growth [39]. Further, it is known that stiffness of the culture biomatrix affects tumour cell phenotypes, such as chemosensitivity, therefore incorporating a matrix is likely critical for cancer culture platforms [2,40,41]. The use of a 3D matrix, as is typical in many engineered culture models however, significantly increases the complexity of image-based single cell analysis as these models are typically formed into a thick gel plug geometry with a curved meniscus surface profile.…”
Section: Introductionmentioning
confidence: 99%